Multi-Signal Virtual Keyboard (MSVK): Use of various sensors to replace the standard keyboard - First steps - Saif, Muhammad Bilal; Neubert, Michael; Spengler, Sebastian; Felzer, Torsten; Rinderknecht, Stephan; Beckerle, Philipp (ACM International Conference Proceeding Series, 2014)
Interaction of computer and people with physical disabilities (who are not capable of using classic input devices) is the main focus of this work. A new system "Multi-Signal Virtual Keyboard (MSVK)" is proposed. MSVK is designed by keeping in view the easiness of use and the speed for data entry. OnScreenDualScribe (OSDS) system is developed by the same group. This system uses 18 keys to emulate the behavior of keyboard and mouse. In this work, the hard keys of OSDS are replaced by wearable sensors. To prove the effectiveness of the new system, it has been tested on three volunteers and promising results have been seen.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Bluetooth; Central controller (CC); Human computer interaction (HCI); Multi-Signal Virtual Keyboard (MSVK); Wearable sensors; ZigBee